TINGKAT ADOPSI TEKNOLOGI PENGENDALIAN HAMA TERPADU PETANI PADI (Studi Kasus Di Kecamatan Sungai Kakap Kabupaten Kubu Raya) - Jajat Sudrajat, Achmad Jailanis, Novira Kusrini, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
Plant Pest Organisms disruption on rice cultivation is increasing, the control carried out by the farmers have not succeeded to the maximum, the effects of climate change are difficult to predict. Both can be very threatening productivity of rice plants in the district Kakap River. Control methods that have been recommended by the PP. No.6 1995, protection of plants which is the basic foundation for addressing attacks Plant Pest Organisms Disorder with Integrated Pest Management system. The application of technology by farmers properly and sustainably need to be known, the study aims: (1) to determine the level of adoption of these technologies participating farmers. (2) to determine the factors associated with the level of farmer adoption of Integrated Pest Management technology participants. The elements of Integrated Pest Management (IPM) technology are; utilization of natural enemies, agroecosystem management, mechanical physical control, pesticide control and control the group. Variables related to the level of adoption of Integrated Pest Management (IPM) technology participating farmers are; farmers age, formal education, non-formal education, farming experience, vast arable land, the ownership status of claim, cosmopolitan and income of farmer. The descriptive method of research that studies the problems of the farming community, relations activities, attitudes, outlook and ongoing process. Population census method used by the four groups of farmers who have been following the activities of the SL-IPM as many as 100 people, to analyze the data using Chi Square test. The results of the study generally indicates the level of participant farmer adoption of IPM technologies in the medium categories means participant farmers of IPM technology is not according with the recommendation. So the IPM technology training through the SL-IPM still needed to farmer groups. Keywords: Plant Pest Organisms disruption, level of adoption, IPM technology